CONTINUING EDUCATION IN THE LIFE STRATEGIES ADULTS - Tarkhanova, Irina; Upeniece, Irena; Arnis, Voldemārs (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
Developing the ability to independently design their lives, creating an image of your future is the key competence of the adult. In this paper we describe the research conducted by the authors factor of continuing education in the life strategies of modern adults. These statistics demonstrate the relationship value of education to solve the problems of adaptation to the new conditions of life.